Innovations in Curriculum Designs Do Not Guarantee Students’ Patient-Centered Attitudes Running Title: Curricula and Patient-Centered Attitudes - Pereira,Claudia Maria Alves da Silva (2019)
ABSTRACT Background Medical schools all around the world are engaged in curricular reforms aimed at fostering patient- and learner-centeredness, implementing curricular transformations in order to counterbalance the erosion of humanistic and professional values and the loss of idealism of recent graduate physicians. In Brazil, medical schools are facing the challenge of redesigning medical curricula towards more learner-centered and patient-centered approaches, stimulated by recent national medical education guidelines. However, desirable outcomes towards medical education have not been fully achieved. Aim To access medical students’ attitudes and determine predictors of medical students’ patient-centered attitudes among students from different curricular designs (traditional, innovative and advanced). Methods Medical students from 1st to 6th year from 21 Brazilian medical schools participating in the project for evaluating change and trends proposed by the Brazilian Association of Medical Education, with different stages of curricular designs (traditional, innovative and advanced), answered the Brazilian version of the Patient–Practitioner Orientation Scale (B-PPOS) and a questionnaire with curricular and sociodemographic variables. Results Brazilian medical students care more than they share information, power and responsibility (p < 0.001; d = 0.599). They are more concerned with the psychosocial context than with patient’s perspective (p < 0.001; d = 0.797) and share more power and responsibility than understanding (p < 0.001, d = 0.455). Female gender (B = 0.180), students from public schools (B = 0.132), year of medical training (B = 0.021), preference for future medical practice in public services (B = 0.053) and extracurricular activities (B = 0.068) were predictors of patient-centered attitudes among medical students (p < 0.05). Meanwhile, the father’s educational level and choice to study surgical specialties (p < 0.05) were predictors of less patient-centered attitudes among students. Different curricular designs were not associated with students’ patient-centered attitudes (p > 0.05). Conclusion tant predictors of patient-centered attitudes among medical students. Further research should investigate the direct influence of faculty professionalism development programs on students’ patient centered-attitudes.